Ordinary stoichiometry of extraordinary microorganisms. Issue 1 (27th August 2015) - Neveu, M.; Poret‐Peterson, A. T.; Anbar, A. D.; Elser, J. J.
Abstract: All life on Earth seems to be made of the same chemical elements in relatively conserved proportions (stoichiometry). Whether this stoichiometry is conserved in settings that differ radically in physicochemical conditions (extreme environments) from those commonly encountered elsewhere on the planet provides insight into possible stoichiometries for putative life beyond Earth. Here, we report measurements of elemental stoichiometry for extremophile microbes from hot springs of Yellowstone National Park (YNP). Phototrophic and chemotrophic microbes were collected in locations spanning large ranges of temperature (24 °C to boiling), pH (1.6–9.6), redox (0.1–7.2 mg L −1 dissolved oxygen), and nutrient concentrations (0.01–0.25 mg L −1 NO 2 −, 0.7–12.9 mg L −1 NO 3 −, 0.01–42 mg L −1 NH4 +, 0.003–1.1 mg L −1 P mostly as phosphate). Despite these extreme conditions, the microbial cells sampled had a major and trace element stoichiometry within the ranges commonly encountered for microbes living in the more moderate environments of lakes and surface oceans. The cells did have somewhat high C:P and N:P ratios that are consistent with phosphorus (P) limitation. Furthermore, chemotrophs and phototrophs had similar compositions with the exception of Mo content, which was enriched in cells derived from chemotrophic sites. Thus, despite the extraordinary physicochemical and biological diversity of YNP environments, life in these settings, in a stoichiometric sense, remains much the same as we know it elsewhere.